MEMBUDAYAKAN NAVIGASI MASA DEPAN KEPEMIMPINAN PENDIDIKAN ISLAM DI MADRASAH - Siswadi Siswadi (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the concept of cultivating future navigation in Islamic educational leadership in madrasas amidst the challenges of the digital era. The study employed a qualitative approach with library research sourced from various scientific literature from the past five years. Data were collected through a systematic search of academic databases and then analyzed using content analysis and thematic analysis techniques. The results indicate that future navigation in educational leadership is a strategic ability to interpret change, design a long-term vision, and manage uncertainty adaptively and innovatively. Islamic educational leadership in madrasas is characterized by the integration of spiritual values ​​with modern managerial practices. However, in its implementation, madrasa leadership faces various challenges, such as low digital literacy, limited technological infrastructure, and resistance to changes in organizational culture. Therefore, a strategy is needed to cultivate future navigation through strengthening vision, developing an adaptive organizational culture, enhancing human resource competencies, Islamic value-based digital transformation, and participatory and data-driven leadership. This research provides a theoretical contribution to the development of a visionary, adaptive, and sustainable model of Islamic educational leadership.